2018
DOI: 10.2478/tar-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy and the Printing Resolution Comparison of Different 3D Printing Technologies

Abstract: The article presents a research conducted with the project: ‘Additive technology used in conduction with optical methods for rapid prototyping of 3D printed models’ [13]. In this article selected three different 3D printing technologies: Fused Deposition Modeling (FDM), Selective Laser Sintering (SLS) and Material Jetting (MJ). Each of them was tested paying special attention to accuracy and resolution of printed elements. Accuracy tests were conducted on the reference specimens which also showed material text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Layer height is also an important printing setting to consider as it directly impacts the quality of a printed object [11,17]. Indeed, a low layer height increases the smoothness of a surface and details of a print, but it lengthens the printing time as layers are deposited, cured or sintered according to the 3D printing technology chosen [17,101]. Conversely, larger layer thickness results in a poor resolution with a rough surface in a shorter printing duration [17,101].…”
Section: Mechanical and Kinematic Specificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Layer height is also an important printing setting to consider as it directly impacts the quality of a printed object [11,17]. Indeed, a low layer height increases the smoothness of a surface and details of a print, but it lengthens the printing time as layers are deposited, cured or sintered according to the 3D printing technology chosen [17,101]. Conversely, larger layer thickness results in a poor resolution with a rough surface in a shorter printing duration [17,101].…”
Section: Mechanical and Kinematic Specificationsmentioning
confidence: 99%
“…Indeed, a low layer height increases the smoothness of a surface and details of a print, but it lengthens the printing time as layers are deposited, cured or sintered according to the 3D printing technology chosen [17,101]. Conversely, larger layer thickness results in a poor resolution with a rough surface in a shorter printing duration [17,101]. Moreover, experimental studies have demonstrated the impact of layers height on the tensile and compressive strength of printed parts [97,102].…”
Section: Mechanical and Kinematic Specificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has to be done carefully and there exists the risk of damaging the model, or inadvertently removing small features. When using soluble support material, there is a lower risk of damaging the model [31] The support structures can be dissolved in water or with a chemical called Limonene. Examples of soluble materials are HIPS (used as a support with ABS material) and PVA (used as a support with PLA material) b) Powder removal (SLS and Powder Bed Fusion) Models printed using powder bed fusion (SLS, etc) are fabricated using plastic or metal powders.…”
Section: Cleaning A) Removing Support Materials (Fdm and Materials Jetting)mentioning
confidence: 99%
“…The purpose of this article is to recognize macro-and microstructure of selected both 3D printing technologies and materials which are described in [1], [2]. It is suspected that the 3D printing process can create a different structure and material behaviour during load than other technologies.…”
Section: Introductionmentioning
confidence: 99%